Studi Induksi Mutasi Genetik Pisang Barangan Melalui Aplikasi Iradiasi Sinar Gamma Secara In Vitro - Zarmiyeni Zarmiyeni; Ishak Ishak (Rawa Sains: Jurnal Sains STIPER Amuntai, 2012)
The study of mutation genetic induct Barangan banana by irradiation gamma ray according in vitro aimed to learning and evaluate dose irradiation gamma ray in to increase various of genetic planet barangan banana that regeneration of shoot tip by direction to withered ache. More 20 shoot tip each in irradiation by 10 Gy and 20 Gy, and countrat as different. Planet in to regeneration in MS media to contain 3 mg/ 1 BAP and 0,5 mg/ 1 IAA. Result accuration showed percentation bud was grow after irradiation Gy 80% Irradiation, 20 Gy 75% Irradiation and 85% countrol. Irradiation dose to affect sum propagoula produce. The increase of irradiation dose tedence to increase sum propagoula produce. The propagoula produce of this accuration was 5 sort that 15 planet, shoot, bud, bud group and nodule